The Buddhist Real Concept of Peace in Theory and Up Wards (Pa?isotag?m?) Practice Which Towards on Philosophical Revelation (Journal of Advanced Research in Social Sciences, 2019)
In a fast-changing world different social institutions and organizations have emerged in order to maintain the well-being or the harmonious existence of human beings and much contribution has been done in the maintenance and the promotion of well-being of humanity. However, the modern era with its rapid developments confronted with many challenges such as environmental pollution, serious health issues, population growth and scarcity of food & sheltered specially the direct man-made issues related to the peace and co-existence of humanity. As a result, physical, social, mental and spiritual well-being has been greatly affected and damaged. Buddhist teachings emphasize that peace is dependent on the physical, social, mental and spiritual well-being of individuals living up wards in any society. Thus, it signifies a state of harmony and friendship, calmness and quietness and also the freedom from war and violence. Hence in the achievement of harmony and peace most significant is the identification and verification of the fundamental issues with impartiality, justice and honesty that lead to the warfare between the nations or countries which is the Buddhist standpoint. In the modern world warfare takes place from many aspects. They have been able to avoid such which is the only fact that humanity can be proud of in this civilized world. However, the situations within some countries are not satisfactory especially in some Asian and Middle East countries where there is divesting warfare between the divided groups who have the underhand support by the powerful.Such lead to the attitudinal change in the people where as their social consciousness becomes widened and deepened. Thus, the attitudinal change gradually takes place which is the key factor for lasting peace in the sustainable developmental countries. Thus (a) Respect for morality (b) Attitudinal change (c) Widening of social consciousness (d) Establishment of higher ideals are the key elements found in Buddhist teachings in theory and upwards practice.